Synchrony in the onset of mental state understanding across cultures?: a study among children in Samoa - Mayer, Andreas Frank; Träuble, Birgit (International journal of behavioral development, 2013)
The development of false belief understanding in Samoa was investigated in two studies testing more than 300 children. Children’s understanding was assessed with a change of location task. The results of study 1 suggest that Samoan children improve gradually and slowly, with no succeeding majority before 8 years of age. One third of the 10-13-year-olds still failed. Study 2 used a different translation among 55 children from 4-8 years of age and supports the former results. These findings speak for the cultural variability of theory of mind development and provide the first cross-cultural continuous survey on false belief understanding of children older than 5 years of age with a large sample in a place where mental states are no suitable object for conjecture.
First Published August 3, 2012
Gesehen am 07.07.2021